Evaluation of polyesteramide (PEA) and polyester (PLGA) microspheres as intravitreal drug delivery systems in albino rats. (April 2017) - Peters, Tobias; Kim, Seong-Woo; Castro, Vinicius; Stingl, Krunoslav; Strasser, Torsten; Bolz, Sylvia; Schraermeyer, Ulrich; Mihov, George; Zong, MengMeng; Andres-Guerrero, Vanessa; Herrero Vanrell, Rocio; Dias, Aylvin A.; et al.
Abstract: Purpose: To study the suitability of injectable microspheres based on poly(ester amide) (PEA) or poly lactic-co-glycolic acid (PLGA) as potential vehicles for intravitreal drug delivery in rat eyes. Dexamethasone-loaded PEA microspheres (PEA + DEX) were also evaluated. Methods: Forty male Sprague Dawley rats were divided into four groups that received different intravitreally injected microspheres: PEA group (n = 12); PLGA group (n = 12); PEA + DEX group (n = 8); and control group (no injection, n = 8). Electroretinography (ERG), fundus autofluorescence (FAF), and spectral domain optical coherence tomography (sdOCT) were performed at baseline, weeks 1 and 2, and months 1, 2, and 3 after intravitreal injection. Eyes were histologically examined using light microscopy and transmission electron microscopy at the end of the in vivo study. Results: There were no statistically significant changes in ERG among the groups. Abnormal FAF pattern and abnormal deposits in OCT were observed after injection but almost completely disappeared between week 2 and month 3 in all injected groups. GFAP staining showed that Müller glia cell activation was most pronounced in PLGA-injected eyes. Increased cell death was not observed by TUNEL staining at month 1. In electron microscopy at month 3, the remnants of microparticles were found in the retinal cells of all injected groups, and loss of plasma membrane was seen in the PLGA group. Conclusions: Although morphological changes such as mild glial activation and material remnants were observed histologically 1 month and 3 months after injection in all injected groups, minor cell damage was noted only in the PLGA group at 3 months after injection. No evidence of functional abnormality relative to untreated eyes could be detected by ERG 3 months after injection in all groups. Changes observed in in vivo imaging such as OCT and FAF disappeared after 3 months in almost all cases.